Willow growth response to altered disturbance regimes in Rocky Mountain National Park: herbivory, water levels, and hay production - Contento, Taryn Elizabeth, author; Sueltenfuss, Jeremy, advisor; Schultz, Courtney, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2021)
Disturbances are essential to the perpetuation of functioning riparian areas. However, with westward expansion, riparian areas, with access to water, fertile soils, and abundant vegetation, have been the target of heavy human use and alteration. Disturbance regimes in riparian areas have been modified, and, as a result, riparian systems and their associated vegetation have been in decline across the United States. The west side of Rocky Mountain National Park (RMNP) in the Kawuneeche Valley has a history of human use and landscape level modification ranging from altered elk and moose populations, hydrological modification from trans basin diversions, and a history of vegetation removal from hay production. This study sampled willow growth (height, cover, and annual growth) response to these overlapping altered disturbances in the Kawuneeche Valley. We found that the largest influence on willow growth was a high level of herbivory that could be attenuated by exclosures. Depth to water level did not significantly relate to willow growth, but a possible -100 cm water level threshold could explain conditions below which water levels would influence growth. Lastly, hay production decreased the overall presence of willows and therefore cover. Future research is needed to explain mechanisms behind these trends but the high levels of browse and decreased overall vigor of willows in the Kawuneeche Valley indicate increased management needs.
Keywords: elk; Rocky Mountain National Park; willow; herbivory; browse; salix